The National Survey on Drug Use and Health Mental Health Surveillance Study: calibration analysis - Aldworth, Jeremy (Int J Methods Psychiatr Res, 2010)
The Mental Health Surveillance Study (MHSS) is an ongoing initiative by the Substance Abuse and Mental Health Services Administration to develop and implement methods for measuring the prevalence of serious mental illness (SMI) among adults in the USA. The 2008 MHSS used data from clinical interviews administered to a sub‐sample of respondents to calibrate mental health screening scale data from the National Survey on Drug Use and Health (NSDUH) for estimating the prevalence of SMI in the full NSDUH sample. The mental health scales included the K6 screening scale of psychological distress (administered to all respondents) along with two measures of functional impairment (each administered to a random half‐sample of respondents): the World Health Organization Disability Assessment Schedule (WHODAS) and the Sheehan Disability Scale (SDS). The Structured Clinical Interview for DSM‐IV (SCID) was administered to a sub‐sample of 1506 adult NSDUH respondents within 4 weeks of completing the NSDUH interview. Results indicate that while SMI prediction accuracy of the K6 is improved by adding either the WHODAS or the SDS to the prediction equation, the models with the WHODAS are more robust. The results of the calibration study and methods used to derive prevalence estimates of SMI are presented. Copyright © 2010 John Wiley & Sons, Ltd.